Identification of a Novel Streptomyces sp. Strain HU2014 Showing Growth Promotion and Biocontrol Effect Against Rhizoctonia spp. in Wheat - Zhu, Hong-Xia (Plant disease, 2023)
Wheat sharp eyespot is a serious disease caused by the phytopathogens Rhizoctonia cerealis and R. solani. Some species in the genus Streptomyces have been identified as potential biocontrol agents against phytopathogens. In this investigation, the physiological, biochemical, phylogenetic, and genomic characteristics of strain HU2014 indicate that it is a novel Streptomyces sp. most closely related to Streptomyces albireticuli. Strain HU2014 exhibited strong antifungal activity against R. cerealis G11 and R. solani YL-3. Ultraperformance liquid chromatography-mass spectrometry on the four extracts from the extracellular filtrate of strain HU2014 identified 10 chemical constituents in the Natural Products Atlas with high match levels (more than 90%). In an antifungal efficiency test on wheat sharp eyespot, two extracts significantly reduced the lesion areas on bean leaves infected by R. solani YL-3. The drenching of wheat in pots with spore suspension of strain HU2014 demonstrated a control efficiency of 65.1% against R. cerealis G11 (compared with 66.9% when treated by a 30% hymexazol aqueous solution). Additionally, in vitro and pot experiments demonstrated that strain HU2014 can produce indoleacetic acid, siderophores, extracellular enzymes, and solubilized phosphate, and it can promote plant growth. We conclude that strain HU2014 could be a valuable microbial resource for growth promotion of wheat and biological control of wheat sharp eyespot